Liberating Accounting with a Religio-Cultural Approach - Virginia Nur Rahmanti; Tjiptohadi Sawarjuwono (Journal of Accounting and Investment, 2020)
Research aims: Accounting as a product of Western thought is believed to be loaded with masculinity values such as selfish, rationalist, materialist, and objective. The Western perspective of social reality runs counter to the Islamic philosophy of religiosity. Capitalism in pragmatic accounting has led to religio-cultural anomalies that have resulted in injustice, domination, and the formation of a class society. This study aims to liberate accounting from masculine characteristics by using Islamic values.Design/Methodology/Approach: The effort to liberate pragmatic accounting in this study is in line with the thoughts of Ali Ashgar Engineer (1999). He uses Islamic theology as a fundamental in carrying out liberation. At the methodological stage, this research uses historical studies (historical research) which is extended by phenomenology. Apart from being aimed at identifying Islamic values, historical research is also applied to find out how these values are used to criticize pragmatic accounting. Meanwhile, the phenomenological methodology is used to understand how religious values can create prosperous accounting.Research Findings: The results showed that monotheism, justice, brotherhood, benefit, balance, gratitude, sincerity, and blessings are Islamic values that are often used by researchers to criticize pragmatic accounting. Analysis of a collection of empirical articles also proves that pragmatic accounting is indeed full of masculinity. By using business as an accounting metaphor, internalization of Islamic values is proven to be able to create a prosperous business. Thus, the internalization of Islamic values will be able to liberate accounting from masculinity.Theoretical constribution/Originality: This research is expected to provide insight into accounting studies using a different approach to previous research, namely by using the basis of Islamic theology.